2015
DOI: 10.5604/15093492.1157092
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-up of Subcutaneous Achilles Tendon Lengthening in the Treatment of Spastic Equinus Foot in Patients with Cerebral Palsy

Abstract: STRESZCZENIEWstęp. Spa stycz na sto pa koń ska jest jed ną z naj czę ściej wy stę pu ją cych de for ma cji w mó zgo wym po ra że niu dzie cię cym. Opty mal ne le cze nie te go ty pu de for ma cji na dal po zo sta je nie usta lo ne. Po mi mo du żej licz by ist nie ją ce go pi śmien nic twa do ty czą -ce go te ma tu mó zgo we go po ra że nia dzie cię ce go, brak jest wy star cza ją cej licz by ba dań o dłu go ter mi no wym cza sie ob ser wa cji po prze pro wa dza nych za bie gach ko rek cyj nych. Ce lem pra cy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…More recently Krupinski et al presented a long-term followup, an average of 10 years, of subcutaneous Achilles tendon lengthening in the treatment of spastic equinus foot in patients with cerebral palsy, after Hooke's or White's isolated procedure. Although the recurrence of the deformity was reported in 43.42% of the patients, the Authors affirm that subcutaneous Achilles tendon lengthening is not associated with a risk of serious complications, while providing good long-term therapeutic outcomes as well as very good cosmetic and functional effects, minimizing the costs and time of patients' hospitalisation 89 . Farshad et al proposed, with an in vitro study, a new method for tendon -lengthening preserving a degree of tendon continuity.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 80%
“…More recently Krupinski et al presented a long-term followup, an average of 10 years, of subcutaneous Achilles tendon lengthening in the treatment of spastic equinus foot in patients with cerebral palsy, after Hooke's or White's isolated procedure. Although the recurrence of the deformity was reported in 43.42% of the patients, the Authors affirm that subcutaneous Achilles tendon lengthening is not associated with a risk of serious complications, while providing good long-term therapeutic outcomes as well as very good cosmetic and functional effects, minimizing the costs and time of patients' hospitalisation 89 . Farshad et al proposed, with an in vitro study, a new method for tendon -lengthening preserving a degree of tendon continuity.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 80%
“…All the joints could be involved, but usually, lower extremities are mostly affected. The advantages of minimally invasive percutaneous multilevel surgery for the treatment of CP are widely treated in the literature [19,20,28,[31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The type of cerebral palsy was reported in thirteen studies, where one study reported a mixed CP type [41]. Twelve studies reported spastic CP [18,21,24,25,28,[30][31][32]35,[43][44][45], and one study reported athetoid CP [25]. The type of equinus was reported six studies, where one study reported static equinus [21] and five studies reported fixed equinus [18,26,[31][32][33].…”
Section: Study Characteristicsmentioning
confidence: 99%